Instrukcijos cenzoriams: pokario Lenkijos cenzūros užkulisiai - Tarvydaitė, Dominyka (Lietuvos istorijos studijos, 2023)
Rec.: Anna Wiśniewska-Grabarczyk, Censorship of Literature in Post-War Poland: In Light of the Confidential Bulletins for Censors from 1945 to 1956, Jagiellonian University Press, 2022.